Feminist Legacies. (2016) - Engle, Karen
Abstract : In February 2013, Navi Pillay, then UN High Commissioner for Human Rights, gave a speech to the General Assembly reflecting on the twenty years that had passed since the Vienna World Conference on Human Rights. She discussed three principal achievements of the Vienna Declaration and Programmeof Action, two of which were "its role in advancing women's rights" and "its impact on the fight against impunity." With regard to the first, she discussed the success of the "Women's Rights are Human Rights" slogan at the conference and the institutional gains it spawned around violence against women(VAW). As for the second, she noted that "[p]erhaps most significantly, just one month after the establishment of the first ad hoc tribunal since Nuremberg [the ICTY], the Declaration nudged the International Law Commission to continue its work on a permanent international criminal court." Although Pillay did not connect those two achievements—the recognition of women's human rights and a new focus on impunity alongside international criminal responses to combat it—they were in fact intertwined.